Videoconferencing as tool of Higher Education - Caporali, Enrica; Trajkovik, Vladimir; Valdiserri, Juna (Springer Berlin Heidelberg, 2010)
In the decade up to 2020 European Higher Education will have a vital contribution to realize a Europe of knowledge that has a relevant role, at national and international level, in the cultural and economical development of countries. The higher education will also face the major challenges and opportunities of globalization with accelerated technological developments with new providers, new learners and new types of learning. New educational requirements stimulated by the innovative telecommunication technologies, leads, almost as direct consequence, to the latest educational materials and methodologies, to videoconferencing and distance learning issues. In this framework, the three-year ViCES (Video Conferencing Educational Services) Project was launched and financed by the European Commission within the TEMPUS (Trans-European Mobility Scheme for University Studies) programme. The VICES project will provide an environment that increases student and academic mobility as well as infrastructure that will ease the process of harmonization of different curricula outcomes.
Keywords: higher education, TEMPUS European Programme, innovative educational methods, distance learning, curricula harmonization, national and international cooperation